A STUDY OF WEAR OF AGED ALUMINUM ALLOYS 2XXX AND 6XXX WITHIN THE MANOVA STATISTICAL ANALYSIS - Meyveci, A.; Karacan, I.; Firat, E. Hanifi; Caligulu, U.; Durmus, H. (Springer, 2011)
Statistically processed data on the microstructure and wear of aged aluminum alloys AA2024 and AA6063 are presented. Results of wear tests are analyzed using multidimensional analysis of variance (MANOVA) with 95% confidence interval for statistically significant deviations. It is shown that the temperature and the duration of the aging are statistically significant factors affecting wear of aluminum alloys 2XXX and 6XXX.
Keywords: aluminum alloys; aging; adhesive wear; statistics